Divestitures and the liquidity of the market for corporate assets - Schlingemann, Frederik P.; Stulz, René M.; Walkling, Ralph A. (Journal of Financial Economics, 2002)
The liquidity of the market for corporate assets plays an important role in explaining whether a firm divests a business segment, which segment the firm divests, and whether it divests a core segment or an unrelated segment. Firms are more likely to divest segments from industries with a more liquid market for corporate assets, unrelated segments, poorly performing segments, and small segments. Strikingly, the segment with the least liquid market is less likely to be divested than the best-performing segment, while the worst-performing segment is less likely to be divested than the segment with the most liquid market.